Interictal dysphoric disorder in people with and without epilepsy - Zinchuk, Mikhail; Kustov, Georgii; Pashnin, Evgenii; Pochigaeva, Ksenia; Rider, Flora; Yakovlev, Alexander; Hesdorffer, Dale; Hauser, W. Allen; Guekht, Alla (Epilepsia (Copenhagen), 2021)
Objective Interictal dysphoric disorder (IDD) has been regarded as an affective disorder occurring only in people with epilepsy (PWE). Data showing similar characteristics and similar prevalence of IDD in patients with migraine and with psychogenic nonepileptic seizures question the epilepsy‐specific nature of IDD. The aim of the study was to investigate the nature of IDD in people with prevalent epilepsy with mood disorders and people with mood disorders who are free of neurological disease. Methods This is a case–control study, with 142 patients with a confirmed diagnosis of epilepsy and major depressive disorder (MDD; cases) and 222 patients with MDD only (controls). MDD diagnosis was confirmed by a structured clinical interview for Diagnostic and Statistical Manual of Mental Disorders, 4th edition (SCID‐I‐RV). We used the Beck Depression Inventory and the Beck Anxiety Inventory to estimate anxiety and depression levels and the Interictal Dysphoric Disorder Inventory (IDDI) to confirm the presence of IDD. Mann–Whitney U test, Pearson chi‐squared, Spearman correlation, and logistic regression were used. Results No differences were found in the prevalence of IDD between PWE with MDD and people with MDD alone (88.73% vs. 85.13%, χ2 = .96, p = .32). There were no differences between the groups overall or for any IDDI subscales (all p > .05). In both groups, IDD symptoms were grouped with the same incidence and had the same duration and periodicity. IDD was not associated with epilepsy (odds ratio = .84, 95% confidence interval = .40–1.98, p = .72). No significant correlation was found between epilepsy, demographic characteristics, and all IDDI subscales (all p > .05). Notably, patients with IDD suffered from affective disorders longer (6.68 ± 6.82 years vs. 3.7 ± 3.97 years, p = .001) and also received higher scores on all psychometric scales (all p < .05). Significance This study does not confirm the specificity of IDD for epilepsy. The presence of IDD symptoms may be associated with a more severe course of MDD and significant anxiety distress.